The Role of Supplier-Buyer Relationships on the Sustainability of Hydroponic Vegetable Supply Chains in the Cirebon Region - Siska Malia; Citra Citra; Natasyah Fadliyah Putri; Yayat Rahmat Hidayat (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2025)
Amidst challenges such as climate change, and the increasing demand for organic food, hydroponic farming has become an attractive option for farmers and businesses. Seeing this, the supplier-buyer relationship itself plays an important role in meeting market demand for the sustainability of the supply chain. The problem statement for this research is how buyer-supplier relationships and their effects on supply chain sustainability are influenced by the quality of communication (X1), relationship commitment (X2), and cooperation (X3). This research aims to ascertain how cooperation with buyer-supplier relationships, relationship commitment, and communication quality affect supply chain sustainability. With a sample size of 110 respondents12 farmers and 98 buyers. SmartPls 3.0 is the methodology employed. The study's findings indicate that supplier-buyer relationships are positively and significantly impacted by cooperation, relationship commitment, and communication quality. Additionally, supplier-buyer relationships can mediate the impact of these three factors on supply chain sustainability.